SAE Technical Paper Series 2007
DOI: 10.4271/2007-01-0726
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Roof-to-Ground Impact Severity: Video Analysis and Analytical Modeling

Abstract: This paper explores the dynamics of rollover crashes and examines factors that influence the severity of the roof-to-ground impacts that occur during these crashes. The paper first reports analysis of 12 real-world rollover accidents that were captured on video. Roll rate time histories for the vehicles in these accidents are reported and the characteristics of these curves are analyzed. Next, the paper uses analytical modeling to explore the influence that the trip phase characteristics may have on the severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…6 6 This point in the discussion is also an ideal point to observe that one of our conclusions in Ref. 25 The Deceleration Rate for a Rolling Vehicle Next, it can be observed that the rate at which a rolling vehicle decelerates will be determined by the accumulation of the ground plane velocity changes that occur during the rollover. Thus, any factor that influences the ground surface velocity changes will also influence the deceleration rate that the vehicle experiences.…”
Section: Figure 16mentioning
confidence: 74%
See 3 more Smart Citations
“…6 6 This point in the discussion is also an ideal point to observe that one of our conclusions in Ref. 25 The Deceleration Rate for a Rolling Vehicle Next, it can be observed that the rate at which a rolling vehicle decelerates will be determined by the accumulation of the ground plane velocity changes that occur during the rollover. Thus, any factor that influences the ground surface velocity changes will also influence the deceleration rate that the vehicle experiences.…”
Section: Figure 16mentioning
confidence: 74%
“…In a previous paper [25], the authors presented a planar, vehicle-to-ground impact model derived using the principle of impulse and momentum and based on the idealized vehicle-to-ground impact shown in Figure 1.…”
Section: Purposementioning
confidence: 99%
See 2 more Smart Citations